2017
DOI: 10.1016/s2214-109x(17)30418-7
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood linear growth faltering in low-income and middle-income countries as a whole-population condition: analysis of 179 Demographic and Health Surveys from 64 countries (1993–2015)

Abstract: SummaryBackgroundThe causes of early childhood linear growth faltering (known as stunting) in low-income and middle-income countries remain inadequately understood. We aimed to determine if the progressive postnatal decline in mean height-for-age Z score (HAZ) in low-income and middle-income countries is driven by relatively slow growth of certain high-risk children versus faltering of the entire population.MethodsDistributions of HAZ (based on WHO growth standards) were analysed in 3-month age intervals from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 38 publications
10
84
0
1
Order By: Relevance
“…Linear growth faltering is commonly seen in LMICs in the first 2 years of life [26]. Catch-up growth is possible in children older than 2 years, although stunting is often well established by this age in many LMICs.…”
Section: Adolescent Growth and Developmentmentioning
confidence: 99%
“…Linear growth faltering is commonly seen in LMICs in the first 2 years of life [26]. Catch-up growth is possible in children older than 2 years, although stunting is often well established by this age in many LMICs.…”
Section: Adolescent Growth and Developmentmentioning
confidence: 99%
“…Fourth, we followed WHO guidelines in excluding the cases with HAZ magnitudes greater than 6 SD. Future work should examine the sensitivity of these findings to changing these cutoffs (Roth et al, ). We also focused on HAZ because they are the most commonly used metric for assessing stunting and growth faltering internationally.…”
Section: Discussionmentioning
confidence: 99%
“…First, the 3 SD cutoff is biologically arbitrary (Leroy & Frongillo, ; Perumal et al, ). Second, stunting prevalence is more appropriately interpreted as an indicator of deprivation for the entire population (not only among those classified as stunted) (Roth et al, ). Nonetheless, we conduct this exercise to illustrate further issues with using a universal standard.…”
Section: Analysis Planmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an interesting idea that was previously explored for growth faltering among children. 5 In their study, 5 Roth and colleagues recognised that the changes observed in the height-for-age distribution in the first 3 years of life could not be explained solely by individual determinants (eg, wealth).…”
Section: The Charade Of Socioeconomic Body-mass Index Determinantsmentioning
confidence: 99%